Diseño del pavimento flexible utilizando el sistema bitufor como medida sustentable en la carretera costanera Huanchaco – Santiago De Cao, La Libertad, 2018 - Reyes Pozo, Brayan Michel (2019)
In this research work, the road costanera was developed, located betwenn the districs of Huanchaco (province of Trujillo) and Santiago de Cao (province of Ascope), región of La Libertad, where the design of flexible pavement using the bitufor system (metal mesh + slurry seal, located between the taxiway and granular fundation) as a sustainable measure was carried out, for this, the trip was made to the study area, where the description of the current state of the road was made, evidencing that the current taxiway (micropavement) is in poor serviceability conditions of having multiple flaws and gaps reaching the level of the granular base, hindering the trafficability of vehicles, basic engineering studies were also carried out, where the topographic study allowed to determine the flat orography of the study area; the traffic study indicated an IMDA design of 1,055 vehicles per day, classifying as a second class road, with a roadway and two lanes of width 3.30m, which must be paved; the study of soil mechanics was carried out with the excavations of the pits up to a depth of 1.5m, collecting the soil samples and taken to the laboratory for analysis, obtaining the CBR of the subgrade of 12%, classifying as a good subgrade; according to these parameters obtained, the flexible pavement was designed using the AASHTO 93 methodology, obtaining thickness 0.10, 0.25 and 0.30m of taxiways, fundation, subfundation, respectively, and through the cracks reflection criterion (developed by the Belgian road research center) and teh software Bisar 3.0 (program for the evaluation of stresses and deformations in flexible pavements), the new design of the flexible pavement was determined, using the bitufor system, reducing the thickness of the taxiways by 20%(2cm); to finally determine the comparison of costs, resulting in a saving of 9.34% in the material of the hot asphalt mixture that makes up the taxiways.